Penerapan Metode Mind Map dengan Strategi Think-Talk-Write untuk Peningkatan Aktivitas dan Pemahaman Belajar pada Materi Sumber Daya Alam dan Pemanfaatannya - Nuraeni, Ai; Iswara, Prana Dwija; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2019)
This research was based on the teacher centered implementation that still be used so it effected to the low activity and the acquisition of student of 4th gradeÂ  at SDN Pasirbenteng II in Rancakalong Sumedang about Natural Resources subjects. This study aims to determine the planning, implementation, improvement activity and student comprehension about material natural resources using Mind Map method and Think-Talk-Write strategy. The instruments used were teacher performance observation sheets, interview guidelines, field notes, student worksheets and learning outcomes tests. The results showed that it has succeeded improved activity and student comprehension. Teacher performance in cycle 1 in planning achieved 73% and 85% in implementation. The 2nd cycle got planning 93%, and implementation 96%. In Cycle 3 got 97% at planning and 96% at implementation. Student activities, in cycle 1 got 54%, in cycle 2 got 60% and in cycle 3 got 82%. Then, student learning outcomes from the first data collected refer to 56%, in 1st cycle got 59%, 2nd cycle got 69% and then the 3rd cycle increased to 87% and it has exceeded the expectation target in about 85%.